Status of sennosides content in various Indian herbal formulations: Method standardization by HPTLC - Md.Wasim Aktar; Rajlakshmi Poi; Anjan Bhattacharyya (Bangladesh Pharmacological Society, 2008)
Several poly-herbal formulations containing senna (Cassia angustifolia) leaves are available in the Indian market for the treatment of constipation. The purgative effect of senna is due to the presence of two unique hydroxy anthracene glycosides sennosides A and B. A HPTLC method for the quantitative analysis of sennosides A and B present in the formulation has been developed. Methanol extract of the formulations was analyzed on a silica gel 60 GF254 HPTLC plates with spot visualization under UV and scanning at 350 nm in absorption/ reflection mode. Calibration curves were found to be linear in the range 200-1000 ηg. The correlation coefficients were found to be 0.991 for sennoside A and 0.997 for sennoside B. The average recovery rate was 95% for sennoside A and 97% for sennoside B showing the reliability and reproducibility of the method. Limit of detection and quantification were determined as 0.05 and 0.25 μg/g respectively. The validity of the method with respect to analysis was confirmed by comparing the UV spectra of the herbal formulations with that of the standard within the same Rf window. The analysis revealed a significant variation in sennosides content.